Assessing nexus effects of energy use in rural areas: The case of an inter- and intra-household model for Uttar Pradesh, India - Utkur Djanibekov; Varun Gaur (University of Bonn, Center for Development Research (ZEF), 2016)
The focus of our analysis is on nexus issues among energy use, incomes, employment, investment decisions, and agricultural production for meeting food and feed demands, as well as health-related effects on rural households. As an example we investigate potential policies, such as public subsidies for solar panels and increase in non-agricultural employment opportunities, for meeting energy demands and improving rural livelihoods, using an agricultural household dynamic programming model. The model includes two types of households that differ in their socio-economic characteristics - poor and rich as measured by their asset and resource endowments, which are linked through the agricultural contracts such as wage-labor and payment for irrigation supply. Moreover, we differentiate the potential impacts of policies at the intra-household level, with special focus of effects on men, women and children. The case study area is the Uttar Pradesh province of India and the main data source is the household survey. The study shows that state subsidies for solar panels improve energy use, agricultural production and incomes of both households in comparison to the business-as-usual case. Also, interactions among two households with agricultural contracts increase. The policy scenario on increasing non-agricultural employment opportunities do not change much energy use pattern of rural households but substantially improves the income levels of poor household, where such household allocates most of labor force for non-agricultural work. In contrast, the household that is better endowed with agricultural production resources looses from such a policy due to less labor available to manage its farm.
Keywords: C61; D63; J41; O13; Q4; Q12; 330; Nexus; Energy use; Heterogeneity; Rural inequality; Dynamic programming